UTILIZATION OF CHARACTER EDUCATION OF SOCIETY 5.0 ELEMENTARY SCHOOL STUDENTS - Sufriadi; Siti Mayang Sari; Akmaluddin; Lili Kasmini (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This research is a literature review that provides some information related to thephenomenon being discussed in this study. With the assistance of parents, teachers,and the community, this study sought to discover character education as an effort toapply religious, moral, and ethical values to students through science. Charactereducation is crucial for students' character formation and development. Thispotential should be sharpened and mingled appropriately with the goal that thepersonality of every youngster is shaped and grows ideally. Children can easilyenjoy digital media in today's society. The advanced time has positive as well asadverse consequences. The job of instructors and guardians is vital to guide andcontrol how kids manage advanced media so youngsters can utilize the valuableopen doors that exist. Sophisticated media and get the benefits of extremewithhering for yourself and your life. The results of the research can be applied tothe world of education by utilizing digital but with good direction and guidancefrom teachers and parents.